SciPy Recipes : a cookbook with over 110 proven recipes for performing mathematical and scientific computations. - Ayyadevara, Kishore (Packt Publishing, 2017)
With the SciPy Stack, you get the power to effectively manipulate and process your data using the popular Python language. This book will show you how to get the most out of the SciPy Stack to get a better sense of your data. It includes hands-on recipes for using the different components of the SciPy Stack such as NumPy, SciPy, matplotlib ...